Assumptions behind size-based ecosystem models are realistic. (29th January 2016) - Andersen, Ken H.; Blanchard, Julia L.; Fulton, Elizabeth A.; Gislason, Henrik; Jacobsen, Nis Sand; van Kooten, Tobias
Abstract: A recent publication about balanced harvesting (Froese et al ., ICES Journal of Marine Science ; 73: 1640–1650) contains several erroneous statements about size-spectrum models. We refute the statements by showing that the assumptions pertaining to size-spectrum models discussed by Froese et al. are realistic and consistent. We further show that the assumption about density-dependence being described by a stock recruitment relationship is responsible for determining whether a peak in the cohort biomass of a population occurs late or early in life. Finally, we argue that there is indeed a constructive role for a wide suite of ecosystem models to evaluate fishing strategies in an ecosystem context.